Effects of silicon on the growth of maize seedlings under normal, aluminum, and salinity stress conditions. (15th June 2017) - Delavar, Kourosh; Ghanati, Faezeh; Zare-Maivan, Hassan; Behmanesh, Mehrdad
ABSTRACT: The effects of silicon on seed germination and growth parameters of maize seedlings under normal, aluminum (Al), and sodium chloride (NaCl) stress conditions were investigated. The results indicated a dose-dependent relationship between silicon and growth parameters, except for germination attributes.Application of silicon (2 mM) accelerated amylase activity, decreased abscisic acid content, and increased indoleacetic acid and gibberellic acid contents of seedling, The results suggest that the beneficial effects of silicon, at least in part, are mediated by the balance of phytohormones. Exposure to Al (10 mM) significantly decreased all growth parameters of maize seedlings. Application of 2 mM silicon, however, alleviated Al stress and restored almost all growth attributes. Decrease of Al absorption, increase of fructan content, and improvement of amylase activity were considered as the mechanisms of ameliorative function of silicon in Al-stressed maize seedlings. Exposure to silicon, however, did not show beneficial effects on growth parameters of maize seedlings under salt stress conditions.